DATA PROTECTION WITH A LIMIT ACCESS IN MOBILE TELEPHONES IN ENVIRONMENT OF OS ANDROID - Мелешко, О.О.; Болотникова, О.С. (Science-based technologies, 2015)
In this article defined that the objects of the protection are the information contained and processed in the mobile, the rights of the owner og these information,the owner of this device and the rights of the user. Revealed the technical and physical weaknesses which are appropriate for in Android OS. Revealed types of data related to restricted information and needed to protection from intruders. Researched built into the system and additional software that was designed for the protection of information against the attacker for mobile devices. After analyzing this software, defined the levels of protection these products. As a result, determined that the built-in is rather convenient, but only from external attacks, then when from internal attacks such as viruses, more effective is additional software.